Measuring adaptive performance in individuals and teams - Marques-Quinteiro, P.; Ramos-Villagrasa, P.; Passos, A. M.; Curral, L. (Team Performance Management, 2015)
Purpose – While scales were developed to measure individual adaptive performance (IAP), fewer contributions have been done to assess the construct at the team level of analysis. This issue is addressed through two related studies: Study 1 builds on Pulakos et al. (2000) to develop a measure of IAP. Study 2 follows from the results in Study 1 and tests a measure of team adaptive performance (Chan, 1998). Design/methodology/approach – Scale development was done adopting a single level (Study 1) and multi-level (Study 2) structural equations modeling approach. Findings – Results suggest that both measures of individual and team adaptive performance are reliable and show evidence supporting the adequacy of adopting referent-shift methodologies to the measurement and aggregation of team members’ rating of team adaptive performance. Originality/value – The study offers a reliable, parsimonious and easy to apply measure of individual and team adaptive performance in organizational work environments.